Family functionality in the depression of adolescents in the private educational institution "Gran Amauta de Motupe" Lima, 2018. - Nataly Olivera, Andy (2019)
Objective: Determine the influence of family functionality on adolescent depression at the private educational institution "Gran Amauta de Motupe" Lima, 2018. Material and method: The design used was non-experimental, cross-sectional, causal correlational, the instruments used were : the Family Cohesion and Adaptability Assessment Scale, FACES IV, by Olson and the Beck Depression Inventory (IDB-II). Results: The sample consisted of 91 adolescents from fi rst to fifth grade of secondary school between 12 and 17 years of age of secondary level. The general analysis showed a 51.6% minimum depression, 28.5% mild, 10.9% moderate and 8.7% severe. While the family functionality showed 65.9% intermediate functionality and 34% low. Conclusion: Adolescents with lower family functionality tend to have greater depressive symptomatology.